COMPUTER LAB NETWORK DESIGN USING MICROTIK ON SMK DHARMA PANCASILA - Dinur Syahputra; Ellanda Purwawijaya; Fithrie Soufitri; Lina Lina (INFOKUM, 2022)
This research uses Mikrotik to design a computer lab at SMK Dharma Pancasila. After implementing the network built at SMK Dharma Pancasila, Sungai Kanan District, it will be obtained a knowledge that; Networks built with Mikrotik provide cost efficiency because the client does not require high-specification hardware and also does not require certain software. Then the distribution of the network used on the proxy is very useful so that the client's performance can be maximized. And with the network, network administration can be done more easily because it is centralized in Mikrotik.